Stroke in Bahrain: Rising Incidence, Multiple Risk Factors, and Suboptimal Care. Issue 4 (June 2015) - Banna, Mona Al; Baldawi, Hassan; Kadhim, Ali; Humaidan, Hani; Whitford, David L.
The incidence of stroke in Bahrain is rising in the Bahraini population and has nearly doubled over the last 16 years, while the incidence in the non-Bahraini population has not changed. Incidence of stroke in the Bahraini population (110/100 000) is now much greater than in the non-Bahraini population (27/100 000). The Bahraini stroke population is 10 years younger than Western comparators with a much higher prevalence of many of the risk factors for stroke, including diabetes (54%), hypertension (75%) and hyperlipidemia (34%). The combination of an ageing Bahraini population alongside a high prevalence of risk factors suggests a 'ticking time bomb' that is likely to see a continuing rise in the incidence of stroke. The quality of risk factor prevention and hospital-based stroke care is therefore crucial in Bahrain. While 88% of patients were scanned within 24 h and 86% with non-haemorrhagic strokes were commenced on aspirin within 48 h, none of the patients received thrombolysis or were admitted to a stroke unit. Improvement of stroke outcomes in Bahrain could be achieved through implementation of evidence-based measures, including improved risk factor management in primary care and stroke units and thrombolysis in secondary care.